Penentuan Faktor Prioritas Pemilihan Online Travel Agency di Wilayah Bekasi Menggunakan Metode Analytical Hierarchy Process - Rakhmah, Syifa Nur; Wahyuningsih, Sri (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Online travel agent is one of the products of the advancing era that is currently booming. With the advent of online travel agents, the use of online travel in Indonesia is now beginning to be demand. The many conviences and advantages offered bya online travel, then customers are required to be keen to choose an online travel agency. This research was conductes to measure the effectivieness of online travel chosen by customers. By using the criteria in ISO 9001:2008 factors that influence customers satisifaction include Service Quality, Product Quality, Price, Situasional Quality and Personal Quality. This research was conducted on online travel customers in the City ofÂ  Bekasi area with a population of 3,013,851 inhabitants with calculations using the Slovin formula obtained a sampel size 400 respondents. The metod use is the analytical hierarchy process. The results of this study indicate that the first alternative is Traveloka eit a weight value of 1.916 or 47.6%, then Tiket.com with a weight value of 1.018 or 27.7% and finnaly Pegipegi with a weight value of 1.141 or 24.7% and for criteria the main attraction customers in chossinh online travel is Service Quality 27.7%, Procust Quality 24.1%, Price 22.9%, Personal Factor 15.5% and Situasional Factor 9.8%